A Pragmatic Approach to Participation in Forest Management - Ahmad, Shahbaz (Indian Forester, 1998)
The paper proposes a pragmatic approach to participation especially with regards to forest management and outlines the impracticability of the prevalent participation concept. A simple and practical approach of involving the people coupled with consistency and dedication is the hope for the countries struggling with the pressure on their natural resources.